NEW IMAGE OF VAMPIRE IN MODERN LITERARY WORKS - Valentina Widya S (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2010)
Literary works cannot be separated from culture. As Abrams(1998) stated that literary works represent the universe. The relation between literary works and universe is never pure. Nothing is ever pure, being at one with itself, and paradigms are no exception. Between the literary studies paradigm as defined and the cultural studies paradigm advocated there are a range of empirical positions. The object of literary study presumes an equation between the aesthetic and the experiential in which the complexity of life is synthesized with the unity of art. Novel as one of the types of literary work serves the variation and interesting development of topics. A novel may be the portrayal of human reality. Its subject matter may be taken from patterns of life, or set in an imaginative time or place. (Nurgiyantoro, 2002:24). A character builds or appears as the implementation of real world and good author is someone who can bring the character outside the literary works. Vampire myths, legends and folklore have existed throughout the ages all over the world. They have appeared in some shape or form in almost every culture and society. Vampire myths are as old as human civilization. The myths change from culture to culture and from geographical area. The myths have evolved along with the times. Literary works make the character famous and mingle with the culture. The aims of this research are to find out the image of vampire in modern culture. Furthermore the research is to find out the changing image of vampire in literary works. The data of this research are Bram Stoker’s novel Dracula as the representation of vampire character in the early ages and Stephanie Meyer’s novel Twilight as the representation of vampire character in modern culture. Thecharacters in both novels are analyzed by using structural approach which focus on characterization and setting, and mythopoeic approach. The result of this research showed that there is a difference in vampire depiction in both novels. The difference depiction of vampires in the both novel is a result of cultural difference which related to society, psychology, historical background of the novel and build new image of vampire in modern literary works.Keywords: character, changing image, modern literary works, setting,vampire